Principal Managerial Competence in Realizing Excellent and Quality Vocational High Schools at East Borneo - Zaenab Hanim (PT ARRUS Intelektual Indonesia, 2022)
This study aims to describe the managerial competence of principals in turning their schools into centers of excellence. This concept is derived from the experience expressed by the leaders responsible for the development of quality management in public and private vocational high schools at East Borneo. This research is a comparative study that uses a qualitative approach with a case study method at two vocational high schools in East Borneo-collecting data using interview, observation, and documentation methods. Semi-structured interviews were conducted to obtain information and excellent school programs from the six informants who participated in this study. They consist of two principals, two curriculum officers, and two teachers who support the flagship program in their school. The results of this study indicate that the principal leads his school to realize a superior and quality Vocational High School; this is the implementation of their managerial competence. Vocational High Schools are organized to prepare a skilled middle-level workforce to support national development in employment and career selection and develop student competencies to compete globally and create jobs. Public and Private Vocational Schools in East Borneo have great potential to become centers of excellence. The principal's managerial competence supports this. Adequate infrastructure according to standard equipment in the industry. In addition, they apply all the knowledge obtained from school about attitudes, manners, character, and Pancasila student profiles in the studio environment and the community in their environment. The Center for Excellence Vocational School's management responsibilities includes developing policies, conducting research, and proposing ideas to the Directorate of Education. Following that, a schedule of tasks is completed to acquire tangible and intangible infrastructure and mentoring activities related to each vocational school's area of specialization.